The Geriatric Nutritional Risk Index is Independently Associated with Prognosis in Patients with Critical Limb Ischemia Following Endovascular Therapy. Issue 2 (August 2016) - Shiraki, T.; Iida, O.; Takahara, M.; Masuda, M.; Okamoto, S.; Ishihara, T.; Nanto, K.; Kanda, T.; Fujita, M.; Uematsu, M.
Abstract : Objectives: Patients with critical limb ischemia (CLI) have poor overall and limb prognosis. Although nutritional status influences overall prognosis, and the Geriatric Nutritional Risk Index (GNRI) is a widely used, simple and well established nutritional status screening method, the association between the GNRI and the overall and limb prognosis of patients with CLI following endovascular therapy (EVT) has not been explored. Methods: Clinical outcomes were retrospectively evaluated in 473 consecutive patients (74 ± 10 years; 59% male) with CLI who underwent EVT. The GNRI on admission was calculated as follows: [14.89 × albumin (g/dL)] + [41.7 × (body weight/ideal body weight)]. Cox proportional hazard analysis was performed to explore the independent association between the GNRI and mortality and major amputation. Results: Patients (53% ambulatory, 38% wheelchair bound, and 9% bedridden) were divided into two groups based on the median GNRI: the higher group (GNRI ≥ 91.2, n = 237) and the lower group (GNRI < 91.2, n = 236). Median follow up duration after EVT was 11.3 months. Three years after EVT, the survival rate (74% in the higher GNRI, and 48% in the lower GNRI, respectively), and limb salvage rate (92% in the higher GNRI, and 84% in the lower GNRI) were significantly lower in the lower GNRI group. GNRI (hazard ratio [HR], 1.03; 95% confidence interval [CI], 1.01–1.05), along with being wheelchair bound (HR, 1.87; 95% CI 1.17–2.97; vs. ambulatory status), being bedridden (HR, 3.10; 95% CI, 1.63–2.97; vs. ambulatory status), being on hemodialysis (HR, 2.33; 95% CI, 1.49–3.64), and having chronic heart failure (HR, 2.22; 95% CI, 1.44–3.43) were the independent predictors of mortality. The GNRI (HR, 1.04; 95% CI, 1.01–1.07), being bedridden (HR, 4.15; 95% CI, 1.67–10.3; vs. ambulatory status), isolated below knee disease (HR, 2.49; 95% CI, 1.30–4.77), and hemodialysis (HR, 2.44; 95% CI, 1.23–4.85) were independently associated with major amputation. Conclusions: The GNRI on admission was independently associated with mortality and major amputation after EVT in patients with CLI.